Model' strategiceskogo upravlenija razvitiem professional'nogo sporta: masštabno-invariantnyj podchod k regional'noj gosudarstvennoj politike - Buletova, N. E.; Opalev, M. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The problem of ensuring the effectiveness of activities carried out by athletes in professional sports and in sports of the highest achievements is related to: state policy and its resource provision at all levels of government; - with global trends affecting the involvement of national sports institutions. Substantiation of a universal model of strategic management of the development of physical culture and sports at any level of management allows to ensure the concentration of resources and managerial efforts to achieve target indicators with maximum efficiency and long-term effect. The main research methods are: method of historical analysis, comparison and systematization of data, their grouping and graphical analysis method, process approach and scale-invariant approach to object research. Research findings include: generalization of the characteristics of professional sports through the specific properties and features of this part of sports; systematized the composition of documents for strategic planning of the development of physical culture and sports at the federal and regional levels of management; a model of the functioning and development of professional sports is presented in the framework of the process and in the framework of scale-invariant approaches. The conclusions reached by the authors are as follows: the conditions for the development of professional sports and sports of the highest achievements correlate with each other in the formation of sports reserves and state policy for the development of physical culture and sports in the regions and municipalities of the country; identified the priorities and features of the development of professional sports within the process approach, substantiated the advantage of using a scale-invariant approach to the study of professional sports as an object of strategic management.